Improve Student Learning Outcomes in Science Grade IV Elementary Schools With A Google Meet Assisted Project Based Learning (PjBL) Learning Model - Prestiyawati Asa (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research was to improve student learning outcomes in science grade IV elementary schools with a Google meet assisted Project Based Learning (PjBL) learning model.Classroom Action Research (PTK) with three cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle the students who completed after carrying out the post test were 62,50n %. In the second cycle students who completed after carrying out the post test were 87,50%. These results indicate that the Project Based Learning (PjBL) learning model can improve student learning outcomes, especially grade IV science at SDN 1 Wonobodro.